The Shift towards Digital Literacy in Australian University Libraries: Developing a Digital Literacy Framework. Issue 1 (2nd January 2020) - Johnston, Nicole
ABSTRACT: There is a growing focus in Australian university libraries on digital literacy with a number of universities developing digital literacy frameworks and digital literacy programmes for students and staff. The Council of Australian University Library (CAUL) has developed a Digital Dexterity Framework that outlines the skills and capabilities that students will need to succeed in the workforce. In 2019 Edith Cowan University (ECU) Library made the strategic decision to develop a digital literacy framework after extensive benchmarking and environmental scanning on current digital literacy initiatives in university libraries around Australia. Extensive consultation on the framework was undertaken during the development of the framework, with consistent feedback indicating that students need digital literacy skills in order to participate in the workplace of the future. The ECU Digital Literacy Framework outlines the strategies and actions that will be implemented in order to equip students at ECU with digital literacy skills. Future initiatives include a collaboration between the Centre for Learning and Teaching (CLT) and the Library Services Centre to embed digital literacy skills into the curriculum, utilising a Library staff digital capability survey to develop training programmes for staff and the development of a study essential module that includes digital literacy elements.